우리나라 일반인 인플레이션 기대 형성 행태 분석 - 이한규 (14088, 2015)
This paper attempts to investigate the Korean households’ inflation expectations with particular attention to information rigidity. For this purpose, we derive an empirical model from a sticky information model &aacute